Trends in genetic composition of livestock with respect to trypanotolerance and desirable economic traits with special emphasis on mixed farming systems in West and Central Africa - Agyemang, K.; Rege, J.E.O. (International Livestock Research Institute, 2004)
Over the last two to three decades, West Africa has witnessed considerable changes in land use. Unprecedented increases in human population combined with changes in climatic patterns have reduced per capita arable land traditionally available for agricultural production. In the livestock sub-sector, these trends are profoundly affecting not only the density of livestock but also the species and breed composition as well as animal husbandry practices. Using trypanotolerant livestock as an example, the trends in the genetic composition of livestock in West and Central Africa from the 1970s to 2000 are examined. Trypanotolerant cattle populations in countries considered as their home of 'origin' increased substantially, on average by 2.7% per annum from 1985 to 1998, whereas declines averaging -2.2% per annum were recorded in countries where such cattle have been introduced in the last 60 years. The extent of crossbreeding between trypano-susceptible zebu breeds and trypanotolerant cattle was larger in coastal semi-arid, coastal subhumid and humid countries than in inland Sahel and inland forest countries. The drivers of the observed changes are believed to be associated with human population, climate, market forces and government policy. The impacts of some of these drivers were analysed in brief case studies from the West African region. It is concluded that the genetic compositions of livestock populations are changing in some parts of the region where reduction of tsetse populations and increase in human populations have made it possible for the trypano-susceptible breeds to move into areas previously occupied by trypanotolerant breeds. However, due to the fact that trypanotolerant livestock have been shown to have equal or higher productivity than trypano-susceptible breeds, even in zero to low tsetse-challenge areas, and that they have the ability to tolerate other major diseases, they will continue to be an important part of mixed production systems in West Africa, irrespective of presence or absence of tsetse flies in the region. Policies on breed improvement and conservation, habitat preservation, and trade in indigenous livestock are needed to promote proper management and use of trypano-susceptible stock.